Pap Smear Screening for Abnormal Cervix and Clinical Correlation - Hadeel H. Haider; Nadia K. Abduljaleel; Nuha Muhsen Mhebis (Academia Open, 2025)
General Background: Cervical cancer remains a leading cause of morbidity and mortality among women worldwide, particularly in low- and middle-income countries where early detection is limited. Specific Background: The Papanicolaou (Pap) smear offers a simple, safe, and cost-effective screening method to identify precancerous, malignant, and benign cervical lesions, yet its application in Iraq is underutilized. Knowledge Gap: Despite global evidence supporting Pap smear screening, there is limited data correlating cytological findings with clinical profiles among Iraqi women. Aims: This study aimed to evaluate the prevalence of abnormal Pap smear results and their clinical correlations in women attending Basrah Teaching Hospital. Results: In a cross-sectional analysis of 63 women aged 21–60 years, the mean age was 38.1 years; acute cervicitis was the most common finding (74.6%), followed by ASCUS (9.5%), LSIL (6.3%), and cervical atrophy (4.8%). Marital status showed a significant association with abnormal cytology (p < 0.05). Novelty: This research provides region-specific insights into the spectrum of cervical cytological abnormalities and highlights demographic and clinical predictors in an Iraqi cohort. Implications: Findings underscore the necessity of implementing routine Pap smear screening and educational initiatives to reduce cervical cancer incidence and improve women’s health outcomes in resource-limited settings Highlights: High prevalence of acute cervicitis among screened women. Marital status significantly linked to abnormal cytology. Pap smear is a low-cost, effective early detection method. Keywords: Cervical Cancer, Pap Smear, Clinical Correlation, Precancerous Lesions